Ensinar/Aprender ortografia: uma experiência na formação de professores - Menezes, Priscilla Carla Silveira (2008)
The studies in the education area have been defending the importance of forming autonomous teachers that they look for to understand the context in that they act, for that movement to make possible educational interventions with better conditions of the students' learning. In the extent of the teachers' formation, it has been discussed the importance of formative actions that they have as focus the analysis of the needs in the educational formation, as alternative to turn such more significant actions. Concerned with those subjects and with the school failure in the Brazilian education, especially in the children's of the public school literacy, we accomplished this work that aims at to investigate the needs of teachers' of the Fundamental Teaching of the public school formation, in the extent of their students' orthographic difficulties, building with those teachers knowledge on the process of teaching/learning spelling. The study was accomplished at a municipal school of the city of Parnamirim-RN, that offers the Fundamental Teaching I. the approach investigativa is of qualitative nature, where the case study and the research-action were used as methodologies. They participated in the research 7 teachers and 1 coordinator of the institution. For the construction of the data the following instruments were used: glimpsed semi-directing collective and individual, documental analysis, questionnaire and observation, that made possible the triangulation of the data for the content analysis. The main results pointed that the teachers' of that school initial needs were addressed not only to the teaching of the spelling, but also to the formation type that they would receive. We verified although the formative process was favorecedor of sockets of the teachers' conscience: related to the orthographic mistakes, to the strategies used at classroom and to the planning addressed to the teaching of the spelling. Finally, we concluded that the teachers' reflection researched about their own formation needs contributed for (trans)formations of their conceptions and practices related to the teaching of the spelling, even before some found difficulties, so much in the formation as in practice pedagogic developed by the participants